Genomic surveillance detects Salmonella enterica serovar Paratyphi A harbouring bla(CTX-M-15) from a traveller returning from Bangladesh - Nair, Satheesh (PLoS One, 2020)
Whole genome sequencing (WGS) has been used routinely by Public Health England (PHE) for identification, surveillance and monitoring of resistance determinants in referred Salmonella isolates since 2015. We report the first identified case of extended-spectrum-β-lactamase (ESBL) Salmonella enterica serovar Paratyphi A (S. Paratyphi A) isolated from a traveller returning to England from Bangladesh in November 2017. The isolate (440915) was resistant to ciprofloxacin and harboured both the mobile element ISEcp9 –bla(CTX-M-15)-hp-tnpA and bla(TEM-191), associated with ESBL production. Phenotypic resistance was subsequently confirmed by Antimicrobial Susceptibility Testing (AST). S. Paratyphi A 440915 harboured an IncI1 plasmid previously reported to encode ESBL elements in Enterobacteriaceae and recently described in a S. Typhi isolate from Bangladesh. Results from this study indicate the importance of monitoring imported drug resistance for typhoidal salmonellae as ceftriaxone is the first line antibiotic treatment for complicated enteric fever in England. We conclude that WGS provides a rapid, accurate method for surveillance of drug resistance genes in Salmonella, leading to the first reported case of ESBL producing S. Paratyphi A and continues to inform the national treatment guidelines for management of enteric fever.